2014
DOI: 10.4103/0971-6580.155341
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic effect of Dioscorea Pentaphylla on genotoxic effect induced by methyl methanesulfonate in the drosophila wing spot test

Abstract: Objectives:Plants as dietary sources are known to have several chemoprotective agents. Dioscorea pentaphylla is an important medicinal plant, which is often used as edible food. This study was undertaken to evaluate the antigenotoxic potential of D. pentaphylla extracts on the genotoxic effect induced by methyl methanesulfonate (MMS) in the Drosophila wing spot test.Materials and Methods:The somatic mutation and recombination test (SMART) was carried out in Drosophila melanogaster. In transheterogyous larvae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 33 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Actually, a growing number of studies have identified different plants extracts with antigenotoxic potential, such as: Mentha longifolia (Al-Ali et al 2014), Dioscorea pentaphylla (Prakash et al 2014), Lilium candidum (Jovtchev et al 2014), Eucalyptus Gunnii (Bugarin et al 2014), Camellia sinensis (Bhattacharya et al 2014), Curcuma longa (Liju et al 2014), Celtis iguanaea (Borges et al 2013), Solanum paniculatum (Vieira et al 2013), Synadenium umbellatum (Melo-Reis et al 2011), Ginkgo biloba (Vilar et al 2009), and others. Thus, there has been growing interest in finding and using natural plant products to reduce genotoxic and/or carcinogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, a growing number of studies have identified different plants extracts with antigenotoxic potential, such as: Mentha longifolia (Al-Ali et al 2014), Dioscorea pentaphylla (Prakash et al 2014), Lilium candidum (Jovtchev et al 2014), Eucalyptus Gunnii (Bugarin et al 2014), Camellia sinensis (Bhattacharya et al 2014), Curcuma longa (Liju et al 2014), Celtis iguanaea (Borges et al 2013), Solanum paniculatum (Vieira et al 2013), Synadenium umbellatum (Melo-Reis et al 2011), Ginkgo biloba (Vilar et al 2009), and others. Thus, there has been growing interest in finding and using natural plant products to reduce genotoxic and/or carcinogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…[22] In another study, it was found that the different concentrations of Dioscorea pentaphylla significantly inhibit the mutagenic effects induced by a potent mutagen methyl methanesulphonate (MMS). [23] They also found that the methanolic extract was highly antimutagenic in comparison to petroleum ether and chloroform. Thus, due to non-mutagenic effects and protection against known mutagens, CT can provide a rationale for use in chemotherapeutic medicine.…”
Section: Discussionmentioning
confidence: 99%
“…In general, dioscorea is vines, (Kamaruddin et al, 2020;Nasriyah et al, 2011) and contains about 75-84% of starch that includes small compounds, such as proteins, vitamins, lipids, and minerals (Shajeela, 2011). The active compounds in dioscorea, such as steroidal sapogenins, glycans, alkaloids, tannins, and saponins, give the characteristic of spicy and bitter tastes (Prakash et al, 2014).…”
Section: Dioscorea Tubersmentioning
confidence: 99%